Postoperative speech impairment and surgical approach to posterior fossa tumours in children: a prospective European multicentre cohort study. (November 2021) - Grønbæk, Jonathan Kjær; Wibroe, Morten; Toescu, Sebastian; Frič, Radek; Thomsen, Birthe Lykke; Møller, Lisbeth Nørgaard; Grillner, Pernilla; Gustavsson, Bengt; Mallucci, Conor; Aquilina, Kristian; Fellows, Greg Adam; Molinari, Emanuela; et al.
Summary: Background: Brain tumours are the most common solid tumours in childhood. Half of these tumours occur in the posterior fossa, where surgical removal is complicated by the risk of cerebellar mutism syndrome, of which postoperative speech impairment (POSI) is a cardinal symptom, in up to 25% of patients. The surgical approach to midline tumours, mostly undertaken by transvermian or telovelar routes, has been proposed to influence the risk of POSI. We aimed to investigate the risk of developing POSI, the time course of its resolution, and its association with surgical approach and other clinical factors. Methods: In this observational prospective multicentre cohort study, we included children (aged <18 years) undergoing primary surgery for a posterior fossa tumour at 26 centres in nine European countries. Within 72 h of surgery, the operating neurosurgeon reported details on the tumour location, surgical approach used, duration of surgery, use of traction, and other predetermined factors, using a standardised surgical report form. At 2 weeks, 2 months, and 1 year after surgery, a follow-up questionnaire was filled out by a paediatrician or neurosurgeon, including neurological examination and assessment of speech. Speech was classified as mutism, reduced speech, or habitual speech. POSI was defined as either mutism or severely reduced speech. Ordinal logistic regression was used to analyse the risk of POSI. Findings: Between Aug 11, 2014, and Aug 24, 2020, we recruited 500 children. 426 (85%) patients underwent primary tumour surgery and had data available for further analysis. 192 (45%) patients were female, 234 (55%) patients were male, 81 (19%) patients were aged 0–2 years, 129 (30%) were aged 3–6 years, and 216 (51%) were aged 7–17 years. 0f 376 with known postoperative speech status, 112 (30%) developed POSI, 53 (14%) developed mutism (median 1 day [IQR 0–2]; range 0–10 days), and 59 (16%) developed reduced speech after surgery (0 days [0–1]; 0–4 days). Mutually adjusted analyses indicated that the independent risk factors for development of POSI were younger age (linear spline, p=0·0087), tumour location (four levels, p=0·0010), and tumour histology (five levels, p=0·0030); surgical approach (six levels) was not a significant risk factor (p=0·091). Tumour location outside the fourth ventricle and brainstem had a lower risk of POSI (with fourth ventricle as reference, odds ratio (OR) for cerebellar vermis 0·34 [95% CI 0·14–0·77] and OR for cerebellar hemispheres 0·23 [0·07–0·70]). Compared with pilocytic or pilomyxoid astrocytoma, a higher risk of POSI was seen for medulloblastoma (OR 2·85 [1·47–5·60]) and atypical teratoid rhabdoid tumour (10·30 [2·10–54·45]). We did not find an increased risk of POSI for transvermian surgical approach compared with telovelar (0·89 [0·46–1·73]). Probability of speech improvement from mutism reached 50% around 16 days after mutism onset. Interpretation: Our data suggest that a midline tumour location, younger age, and high-grade tumour histology all increase the risk of speech impairment after posterior fossa tumour surgery. We found no evidence to recommend a preference for telovelar over transvermian surgical approach in the management of posterior fossa tumours in children in relation to the risk of developing POSI. Funding: The Danish Childhood Cancer Foundation, the Swedish Childhood Cancer Foundation, the UK Brain Tumour Charity, the Danish Cancer Society, Det Kgl Kjøbenhavnske Skydeselskab og Danske Broderskab, the Danish Capitol Regions Research Fund, Dagmar Marshall Foundation, Rigshospitalet's Research Fund, and Brainstrust.